Intelligent nanotherapeutic strategies for the delivery of CRISPR system - Chao Chen; Wu Zhong; Shiyu Du; Yayao Li; Yunfei Zeng; Kunguo Liu; Jingjing Yang; Xiaoxiang Guan; Xin Han (Elsevier, 2023)
CRISPR, as an emerging gene editing technology, has been widely used in multiple fields due to its convenient operation, less cost, high efficiency and precision. This robust and effective device has revolutionized the development of biomedical research at an unexpected speed in recent years. The development of intelligent and precise CRISPR delivery strategies in a controllable and safe manner is the prerequisite for translational clinical medicine in gene therapy field. In this review, the therapeutic application of CRISPR delivery and the translational potential of gene editing was firstly discussed. Critical obstacles for the delivery of CRISPR system in vivo and shortcomings of CRISPR system itself were also analyzed. Given that intelligent nanoparticles have demonstrated great potential on the delivery of CRISPR system, here we mainly focused on stimuli-responsive nanocarriers. We also summarized various strategies for CIRSPR-Cas9 system delivered by intelligent nanocarriers which would respond to different endogenous and exogenous signal stimulus. Moreover, new genome editors mediated by nanotherapeutic vectors for gene therapy were also discussed. Finally, we discussed future prospects of genome editing for existing nanocarriers in clinical settings.